2020
DOI: 10.1016/j.ophtha.2019.09.036
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Approaches Predict Glaucomatous Visual Field Damage from OCT Optic Nerve Head En Face Images and Retinal Nerve Fiber Layer Thickness Maps

Abstract: Purpose: To develop and evaluate a deep learning system for differentiating between eyes with and without glaucomatous visual field damage (GVFD) and predicting the severity of GFVD from spectral domain OCT (SD OCT) optic nerve head images.Design: Evaluation of a diagnostic technology.Participants: A total of 9765 visual field (VF) SD OCT pairs collected from 1194 participants with and without GVFD (1909 eyes).Methods: Deep learning models were trained to use SD OCT retinal nerve fiber layer (RNFL) thickness m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
101
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(118 citation statements)
references
References 40 publications
(57 reference statements)
6
101
3
Order By: Relevance
“…Other studies relied on different types of OCT inputs to get predictions of SAP. 7,[33][34][35][36][37] Christopher et al 37 achieved best performance when using en face images to predict SAP global metrics and sectoral averages. It should be noted, however, that our main purpose was to use the CNN to develop an SF map.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies relied on different types of OCT inputs to get predictions of SAP. 7,[33][34][35][36][37] Christopher et al 37 achieved best performance when using en face images to predict SAP global metrics and sectoral averages. It should be noted, however, that our main purpose was to use the CNN to develop an SF map.…”
Section: Discussionmentioning
confidence: 99%
“…Although attempts to use machine learning algorithms for structure-function relationships in glaucoma are not novel [38][39][40], there have been few studies that predict visual field using OCT imaging. In a recent study similar to ours, Christopher et al [41] used a deep learning The combined OCT images, which were input into the deep learning architecture, are shown on the left column. The actual threshold values of visual field exams are shown in the (B) middle panel and the threshold values predicted by Inception V3 based deep learning architecture are shown on the (C) right panel.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our research teams from UCSD and UTokyo recently reported the benefits of transfer learning using Imagenet in glaucoma detection from fundus photographs as well as diagnosing early stage glaucoma from optical coherence tomography (OCT) images. 5,6,25,26 In both cases, diagnostic performance of the deep learning model was significantly improved by pretraining using transfer learning. 5,6 Updating the trained model with new images for the same specialized task can also improve performance.…”
Section: Introductionmentioning
confidence: 97%